PROBLEM POSING: MODEL PEMBELAJARAN UNTUK PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Trisnawati, Trisnawati; Kristiana Dewi, Novi Ayu; Pratiwi, Rani (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2019)
Problem solving is one of the competencies that must be achieved in learning, especially mathematics learning. Previous research and pre-survey results show that students' ability to solve problems is still low. Therefore, learning mathematics should be able to stimulate the development of problem solving abilities. One strategy that can be used to develop problem-solving skills is problem posing. Problem posing refers to making questions by students based on certain criteria. Several studies have shown that the ability of problem posing can support the ability of problem solving.